Investigation of laser-matter interaction dynamics - Suresh Kumar M. Singaram. (2009)
A laser matter interaction facility was set up. Optical and x-ray diagnostics were developed and set up. Laser irradiance at the focal plane was increased to a sufficient level by reducing the spot size. The interaction of the laser with various target material was investigated by probing the plasma optically and by observing the emission of x-rays.